Self‐defining memories after severe traumatic brain injury: A preliminary study. Issue 1 (9th June 2020) - Rochat, Lucien; Renaud, Olivier; Arnould, Annabelle; Lardi Robyn, Claudia; Barbot, Frédéric; Azouvi, Philippe; Van der Linden, Martial
Abstract : Autobiographical memory plays a major role in the (re)construction of sense of identity, a recurrent issue after a traumatic brain injury (TBI). Although the recall of specific autobiographical events is frequently impaired in patients with TBI, little is known about how these changes affect their sense of self and identity. Thus, we examined self‐defining memories (SDMs), that is, the most significant personal memories supporting one's sense of identity, in 16 patients with severe TBI and in matched controls. To this end, participants recalled three SDMs and rated their emotions in response to memory retrieval. In addition, characteristics of SDMs such as specificity, meaning‐making, self‐connections that reflect identity stability or identity change, content (theme, presence of tension, and redemption sequences) were analysed by independent raters. The main results showed that patients' SDMs were less specific and contained fewer redemption sequences than did those of controls but did not significantly differ in thematic content, presence of tension, meaning‐making, self‐connections that reflect identity stability or identity change and affective responses to memory retrieval. Furthermore, among the patients' memories that refer to the TBI‐related event itself, only one contained an explicit meaning. Despite the lack of specificity in memories, patients with severe TBI were able to extract meaning from personal memories although they could struggle with integrating the TBI‐related event into their sense of identity. These characteristics of SDMs may contribute to disturbances in sense of self and continuity in patients with severe TBI, as well as difficulties in personal or social adjustment. These results also open up relevant prospects for psychological interventions in identity‐related issues in patients with TBI.